Congenital heart defects in IVF/ICSI pregnancy: systematic review and meta‐analysis. (3rd January 2018) - Giorgione, V.; Parazzini, F.; Fesslova, V.; Cipriani, S.; Candiani, M.; Inversetti, A.; Sigismondi, C.; Tiberio, F.; Cavoretto, P.
ABSTRACT: Objective: There is no consensus in current practice guidelines on whether conception by in-vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) techniques is an indication for performing a fetal echocardiogram. The aim of the study was to assess whether congenital heart defects (CHD) occur more often in pregnancies conceived after IVF/ICSI as compared with those conceived spontaneously. Methods: A systematic search for studies was conducted of PubMed/MEDLINE, EMBASE and Scopus from inception to September 2017. The search included the following medical subject heading (MeSH) terms alone or in different combinations: 'IVF', 'IVF/ICSI', 'ART pregnancy', 'assisted conception', 'birth defect', 'congenital heart defects' and 'congenital malformation or abnormalities'. Studies comparing neonatal incidence of CHD in pregnancies conceived after IVF/ICSI and those conceived spontaneously were included. Studies reporting on other types of assisted reproductive technology (ART) or lacking information concerning termination of pregnancy were excluded. Chromosomal abnormalities were excluded in all analyzed studies. A meta‐analysis of selected cohort studies was conducted to estimate the pooled odds ratio (OR) with 95% CI using a random‐effects model. Statistical heterogeneity among the studies was evaluated with the I 2 statistic and Q ‐test. Results: Forty‐one studies were identified for review including six case–control and 35 cohort studies. Data of eight selected cohort studies were used for meta‐analysis. A total of 25 856 children conceived from IVF/ICSI techniques and 287 995 children conceived spontaneously, involving both singleton and multiple gestations, were included in the analysis. Total CHD events were 337/25 856 (1.30%) and 1952/287 995 (0.68%) in the IVF/ICSI and spontaneous conception groups, respectively. The risk of CHD was significantly increased in the IVF/ICSI group as compared with the spontaneous conception group (pooled OR, 1.45; 95% CI, 1.20–1.76; P  = 0.0001; I 2  = 44%; P  = 0.08). In the subgroup of singleton IVF pregnancies, a significant difference was also obtained (OR, 1.55; 95% CI, 1.21–1.99; P  = 0.0005; I 2  = 36%; P  = 0.18) and also multiple confounding factors adjusted ORs showed statistical significance (pooled OR, 1.29; 95% CI, 1.03–1.60; P  = 0.02; I 2  = 0%; P  = 0.43). Conclusion: Fetuses conceived with IVF/ICSI methods are at an increased risk of developing CHD compared with those conceived spontaneously. However, this finding deserves further investigation due to heterogeneity of both ART procedures and cardiac defects. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.